Controllable Synthesis and Electrochemical Research of Zn2TiO4 Spheres as New Anode Materials for Lithium Ion Batteries. (8th October 2021) - Han, Meng‐Cheng; Zhu, Lan‐Lan; Jiao, Si‐Yu; Yi, Ting‐Feng; Cui, Ping; Shi, Yi
Abstract: Zn2 TiO4 spheres are fabricated via a simple hydrothermal strategy combined with subsequent heating treatment of 600, 700, and 800 °C, respectively. All the as‐synthesized Zn2 TiO4 spheres are assembled by many small nanospheres with a particle size of 20–100 nm. The compactness of Zn2 TiO4 spheres is continuously enhanced as the temperature rises from 600 to 800 °C. Additionally, compared with the Zn2 TiO4 calcined at 700 and 800 °C samples, the Zn2 TiO4 sintered at 600 °C sample exhibits the best electrochemical performance, and it can deliver the high discharge specific capacities of 405, 269, 223, 193, 173, and 166 mAh g –1 at current densities of 50, 100, 200, 300, 400, and 500 mA g –1, respectively. Simultaneously, it also displays the excellent cyclic performance with a high reversible charge (discharge) capacity of 245.8 (247.7) mAh g –1 after 300 cycles at the current density of 200 mA g –1 . The results demonstrate that the as‐prepared ZnTiO4 spheres sintered at 600 °C will be expected to be a new anode material of lithium ion batteries. Abstract : Zn2 TiO4 spheres assembled by many small nanospheres are fabricated via a simple hydrothermal strategy combined with subsequent heating treatment of 600, 700, and 800 °C, respectively. The electrochemical properties of three Zn2 TiO4 samples as anodes of Li‐ion batteries are compared and analyzed. Therein, Zn2 TiO4 sintered at 600 °C displays the largest specific surface area and the best electrochemical performance.